Populasi Hama Wereng Batang Coklat (Nilaparvata lugens Stal.), Keragaman Musuh Alami Predator Serta Parasitoidnya Pada Lahan Sawah Di Dataran Rendah Kabupaten Indramayu - Martua Suhunan Sianipar; Andang Purnama; Entun Santosa; R.C. Hidayat Soesilohadi; Wahyu Daradjat Natawigena; Nenet Susniahti; Akbar Primasongko (Faculty of Agriculture, Pattimura University, 2017)
Population of brown plant hopper (Nilaparvata lugens Stal) is one of the major rice pest that is threatening rice production in Indramayu. Integrated pest management is needed to control the population of brown plant hopper (BPH). To construct effective strategy of Integrated Pest Management, a survey to obtain information about the population of BPH and the diversity of its natural enemies predator and parasitoid is required. The result of the survey showed that fluctuation of BPH population was evidence. BPH occurs from the 1st week of observation and the population was rising until the 5th week of observation and hence the population declined until the 12th week of observation. This population decline was caused by BPH’s live cycle followed the growth phase of rice plant. Correlation between climate factors and fluctuation of BPH population was not significant. Based on Shanon-Wiener diversity index analysis, the diversity of natural predators of BPH was medium with the value of H’ of 1,83 due to uniform field condition